Fra huskult til basilika - Bilde, Per (Religionsvidenskabeligt tidsskrift, 2004)
It is still an astonishing fact that no material remains of early Christian churches have been found antedating the building in Dura-Europos at the Euphrat River in present day Iraq. It was a usual private dwelling house that in 241 was rebuilt and transformed into a Christian cult place. This building, however, in no way resembled the magnificent Christian basilicas that were built from the time of Constantine the Great (ruling 306/324-337), and only the baptistery in the rebuilt houses proves that it actually was a Christian building. In the present article I briefly scetch the history of the development of the Christian cult building from the private meeting places at the time of the New Testament to the Constantinian basilicas. The main purpose, however, is to discuss the character of the Christian cult house in relation to a number of related earlier and contemporary types of buildings such as the classical Hellenistic-Roman temples, the Jewish synagogue and a number of Graeco-Roman buildings that can be reagrded as historical forerunners of the Christian church building: the Greek counsel hall (bouleutêrion), the hall of initiation (e.g. Eleusis), the lecture hall (such as gymnasium and stoa), the Greek and Near Eastern cult theatres, the roman basilica and the Roman mithraeum. From the beginning, obviously, the Christian cult building was a meeting house like the Greek counsel hall, the roman basilica and the Jewish synagogue. But it was also a dining room, and, at least from 241, with thebatistery in Dura-Europos, it also became a hall of initiation. Thus, the Christian cult building developed by uniting a number of eatlier types of buildings, secular and sacred, and from the time of Constantine, the Christian basilica united the secular Greek meeting house, which was continued and further developed in the Jewish synagogue, the Greek hall of initiation, and the classical Graeco-Roman Temple.